1980
DOI: 10.1007/bf00412893
|View full text |Cite
|
Sign up to set email alerts
|

Crude and age-specific incidence of cancer of the stomach, colon, breast, and lung ascertained by autopsy frequency in the Heidelberg area from 1900 to 1975

Abstract: Time independence of the selection of autopsy material of the Institute of Pathology of the University of Heidelberg can be assumed as all factors depending on this selection show a remarkable steadiness during the period covered: The mean age of death of patients on whom an autopsy was performed and was not performed is the same, the sex ratio remains unchanged, the number of persons who died in the Heidelberg area has decreased only slightly, and the percentage of dead patients with last residence in this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus women who live longer will be deemed "cured". This should be considered in the context of the fact that autopsy demonstrated the presence of cancer in humans that was not diagnosed during life (Narod et al, 2015), and also that latent metastases not diagnosed by conventional imaging methods were found in patients with breast cancer (Kayser & Burkhardt, 1980). This, along with an understanding of the metastatic process, is the fundamental basis for the MRD study in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus women who live longer will be deemed "cured". This should be considered in the context of the fact that autopsy demonstrated the presence of cancer in humans that was not diagnosed during life (Narod et al, 2015), and also that latent metastases not diagnosed by conventional imaging methods were found in patients with breast cancer (Kayser & Burkhardt, 1980). This, along with an understanding of the metastatic process, is the fundamental basis for the MRD study in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of recurrences occur in the first 5 years after diagnosis; so long term survivors are more likely to be ‘cured’. This should be considered alongside the fact that old autopsy studies have demonstrated the presence of cancers in people who had otherwise been undiagnosed [ 8 ], and that occult metastases undetectable by conventional imaging have been demonstrated in breast cancer patients [ 9 ]. This, alongside understanding the metastatic process, is the fundamental basis for the need to study MRD.…”
Section: Introductionmentioning
confidence: 99%